Corrosion Inhibition characteristics of Reinforced Steel in H2SO4 by benzoyl Thiourea - Abu alqassim, Zianab; Almahdi, Omhani; Almassri, Omkalthoom; AL-abbassi, Aisha (Journal of Pure & Applied Sciences, 2021)
In The adsorption and corrosion inhibition performance of 3,3-diethyl(4-Chloro)benzoylthiourea, ClDEBT, at reinforced steel in H2SO4 interface was examined using gravimetric method at 303.15 K. The inhibition effectiveness of ClDEBT was improved by increasing the concentration. The adsorption data of ClDEBT on the reinforced steel surface were fitted to Langmuir, Temkin and thermodynamic–kinetic adsorption isotherms, and some thermo-dynamics functions as α, y, f, ΔGads and Kads were obtained. Activation energies of 35.69 and 55.99 kJ mol−1 for the corrosion processes of reinforced steel were observed in presence and absence of benzoylthiourea inhibitor, respectively. The adsorption of thiourea inhibitor on the surface of reinforced steel was found to be spontaneous and exothermic. Quantum parameters as the highest & lowest occupied molecular orbital energy (EHOMO) & (ELUMO), energy gap (ΔE), were determined and correlated to the experimental data.